2017
DOI: 10.1038/nature21697
|View full text |Cite|
|
Sign up to set email alerts
|

MC4R-dependent suppression of appetite by bone-derived lipocalin 2

Abstract: Bone has recently emerged as a pleiotropic endocrine organ that secretes at least two hormones, FGF23 and osteocalcin, which regulate kidney function and glucose homeostasis, respectively. These findings have raised the question of whether other bone-derived hormones exist and what their potential functions are. Here we identify, through molecular and genetic analyses in mice, lipocalin 2 (LCN2) as an osteoblast-enriched, secreted protein. Loss- and gain-of-function experiments in mice demonstrate that osteobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
391
7
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 349 publications
(437 citation statements)
references
References 52 publications
29
391
7
3
Order By: Relevance
“…This study showed that serum LCN2 levels were positively associated with FIns, as well as HOMA-β, the index assessing basal β-cell function, suggesting that LCN2 may contribute to insulin secretion in T2DM. These data are in agreement with the findings in transgenic mice [10]. In these transgenic mice lacking LCN2 in osteoblasts, insulin secretion was shown to be reduced in response to glucose or arginine challenge while islet number and size, β-cell mass, and β-cell proliferation decreased in the pancreas.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This study showed that serum LCN2 levels were positively associated with FIns, as well as HOMA-β, the index assessing basal β-cell function, suggesting that LCN2 may contribute to insulin secretion in T2DM. These data are in agreement with the findings in transgenic mice [10]. In these transgenic mice lacking LCN2 in osteoblasts, insulin secretion was shown to be reduced in response to glucose or arginine challenge while islet number and size, β-cell mass, and β-cell proliferation decreased in the pancreas.…”
Section: Discussionsupporting
confidence: 82%
“…LCN2 was also shown to reduce osteoblast differentiation and be involved in osteoblast-osteoclast coupling [8,9]. The latest study demonstrates that bone is the main source of LCN2 in mice [10]. In agreement to the findings in the animal models mentioned above, this study is the first report showing that serum LCN2 levels correlate to both BMD and BTMs in patients with T2DM.…”
Section: Prace Oryginalnesupporting
confidence: 78%
See 2 more Smart Citations
“…Thus, inhibition of MC receptor activity by infusion of an MC receptor antagonist or with the inverse agonist agouti-related protein results in increased food intake. 76,77) Megestrol acetate improves appetite and is associated with slight weight gain in patients with cancer, AIDS, and other underlying pathology. 78) 3.…”
Section: Orexigenicsmentioning
confidence: 99%